Can anyone help work these problumns out step by step?

11x-37=x+23
10p-26=p-44
-13x+5=4x-6
-7x+13=4x-7
11x+5=17
-11x+13=-42
-15y+26=-19
5x-13=9x+15
6q-14=11q-19
4(-2x-5)=29
12(2-5x)=(3x-1)
9x+2=15x-10
19q+4=7q-3
6(2x+1)=9(2x+6)
-7(x-3)=8(4-5x)
-3(p-4)=8(4-9p)
-(y+15)=7(-5-3y)
6m+5=2m-6
7(2p-3)=5(6p-1)
-(y+12)=9(-7-2y)
-(x+7)=5(-11-5x)
7(2x+4)=28
-(y+12)=9(-7-2y)
-(x+7)=5(-11-5x)
7(2x+4)=28
5(-3x+2)=7
7p-3=2
-3(5p+2)=39
12x-15=21
8y+24=40
6x-15=22
-7(9y-5)=35
2(3x+4)=32
-12(7y-1)=12
4(5x+8)=-3
7(5q-2)=11(3-4q)
12(5x-7)=6(3x-14)
-(x+21)=6(-9-2x)
3(6x-5)=19x-2
6(7y-3)=43y-15
6(2-5x)=3(4-7x)
2(4-7y)=3(3-2y)
-(x-60)=5(12-7x)
7(4x-1)=12(3x-4)
8(2y-1)=12(3y-5)
-(x+40)=10(3x-4)

1 answer

Do mathematical operations,then put unknown values on left side of equation,nubers on right side.

For example:

-(x+40)=10(3x-4)
-x-40=30x-40
-x-30x=-40+40
-29x=0
x=0

-11x+13=-42
-11x=-42-13
-11x=55 Divide with -11
x= -5

9x+2=15x-10
9x-15x= -10-2
-6x= -12 Divide with -6
x=(-12)/(-6)=2

2(4-7y)=3(3-2y)
8-14y=9-6y
-14y+6y=9-8
-8y=1 Divide with -8
y= -1/8